1998
DOI: 10.1046/j.1523-1747.1998.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A Germline Mutations in U.K. Patients with Familial Melanoma and Multiple Primary Melanomas

Abstract: We report six of 16 U.K. melanoma families and two of 17 patients with multiple primary melanomas and a negative family history who have between them four different functionally damaging mutations of the CDKN2A (p16) gene: an Arg 24 Pro substitution in exon 1 in one family, a stop codon at codon 44 of exon 1 in one family, and a Met 53 Ile substitution in exon 2 in four families. One multiple primary melanoma patient also has the Met 53 Ile mutation and a second has a G-T substitution at the IVS2 + 1 splice do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 18 publications
4
53
1
1
Order By: Relevance
“…The first one, a novel p16 INK4a missense mutation, was found in one out of 18 (5%) MPM patients. This result could be in agreement with published reports, in which 9.6% (3/31), 11% (2/17), 9% (9/100), and 3% (2/65) of MPM patients were carriers of INK4a-ARF germline mutations (MacKie et al, 1998;Monzon et al, 1998;Hashemi et al, 2000;Auroy et al, 2001). However, Ala5Thr is most likely a polymorphism as the amino terminus of p16 INK4a prior to the start of the ankyrin repeats is poorly conserved and is believed to have no effect on the stability of p16 INK4a .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The first one, a novel p16 INK4a missense mutation, was found in one out of 18 (5%) MPM patients. This result could be in agreement with published reports, in which 9.6% (3/31), 11% (2/17), 9% (9/100), and 3% (2/65) of MPM patients were carriers of INK4a-ARF germline mutations (MacKie et al, 1998;Monzon et al, 1998;Hashemi et al, 2000;Auroy et al, 2001). However, Ala5Thr is most likely a polymorphism as the amino terminus of p16 INK4a prior to the start of the ankyrin repeats is poorly conserved and is believed to have no effect on the stability of p16 INK4a .…”
Section: Discussionsupporting
confidence: 93%
“…This hypothesis is strengthened by the fact that germline mutations of the INK4a-ARF gene have been detected in some MPMs (MacKie et al, 1998;Monzon et al, 1998;Hashemi et al, 2000;Auroy et al, 2001), and could also predispose to other types of cancers, such as pancreatic cancer (Borg et al, 2000), epidermoid carcinoma (Yarbrough et al, 1996), breast cancer (Borg et al, 2000), or multiple myeloma (Dilworth et al, 2000) in melanoma families.…”
mentioning
confidence: 99%
“…In melanoma, as well as other 9p21-associated cancers, the 9p21 region most commonly sustains homozygous deletions in sporadic cases (see references in Funk et al 1998; Haluska and Hodi 1998; Kumar et al 1998;Matsumura et al 1998;Ruiz et al 1998;Wagner et al 1998) and both deletions and point mutations in familial cases (Hussusian et al 1994;Kamb et al 1994;Gruis et al 1995;Fitzgerald et al 1996;Flores et al 1998;MacKie et al 1998;Platz et al 1998;Soufir et al 1998) often eliminating INK4b and INK4a/ARF (for review, see Haluska and Hodi 1998). The high incidence of deletion has fueled an ongoing debate centered on whether each of these genes contributes to the tumor suppressor activity encoded within 9p21.…”
Section: Ink4bmentioning
confidence: 99%
“…According to the results, the R24P missense mutation almost completely abrogates the binding activity of the protein, thus explaining the disease-predisposing nature of the mutation. Following the "New World" publications of the R24P mutation, authors also reported it in European melanoma-prone families: it was reported in 1998 in the UK (MacKie et al, 1998) in the case of a relatively young (y31) male patient with multiple primary melanomas and in the case of two unrelated melanoma-prone kindreds in France (Soufir et al, 1998). This is why review papers from the mid-2000s refer to the R24P mutation as one of the most widespread CDKN2A mutations in the World, contributing to the genetic predisposition to familial, as well as multiple primary melanoma.…”
Section: The R24p Mutation Of Cdkn2a Has Been Worldwide Implicated Asmentioning
confidence: 99%